PENGARUH INFLASI, SUKU BUNGA, DAN KURS TERHADAP INDEKS LQ-45 DI BURSA EFEK INDONESIA PERIODE TAHUN 2007-2011 - Tona Aurora; Agus Riyadi (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
This research aims is to examine empirically the effect of selected macroeconomic variables, i.e., inflation rate, Bank Indonesia Certificate rate, and the exchange rate on IDR of the LQ-45 index in Indonesia Stock Exchange in the period 2007 to 2011. Data analyzes of this research use multiple linier regression and hypothesis with variable independent inflation Bank Indonesia Certificate rate and the exchange rate on IDR towards dependent variable LQ45 index. Data resources of this research is secondary data, that has been collected by the data collector to shows and has been published to the user community.The result shows that only one variable inflation doesn’t influence to the performance of LQ45 index. SBI interest rate and the the exchange rate on IDR is negatively significant. The investors are urged to consider these two fundamentals variables, such as rate SBI and the exchange rate on IDR to invest in the stock market. This research only covers three selected macroeconomic variables. Therefore, further research should examine other potential macroeconomic variables which affect the LQ-45 index. Key words : Inflation, Interest Rate,Exchange Rate, LQ45 index